Determining Predictive Indicators of Marital Boredom Based on Lived Experiences of Couples Referred to Counseling Centers and Convenient Pattern: A Qualitative Research - Fatemi, Seyedeh Maryam; Dayarian, Mohammad Masoud; Mosavi, Seyed Esmail (Applied Family Therapy Journal (AFTJ), 2022)
Aim: One of the psychological disturbances in couples’ relationships is marital boredom; as the emergence of bedrock, psychological problems and the coldness of emotional relationships gradually lead the couple to separation. Therefore, the aim of this study was to investigate the predictive indicators of marital boredom based on couples’ lived experiences. Method: Analysis of qualitative data with phenomenological approach was based on Colaizzi method. Participants included couples referring to counseling centers in Isfahan who were selected by purposive sampling method and according to the inclusion criteria. Individuals’ experiences were examined using in-depth and semi-structured interview tools, and the data were saturated with 23 interviews. Results: In the first stage of coding, 225 basic themes were extracted from the text of the interviews. In the second stage, 22 sub-themes and in the third stage, 7 main themes were identified. Data validation was performed by three methods of receiving feedback from participants, the method of independent coders and the method of a group of experts (3 experts) and the criteria for determining the accuracy and robustness of the data were observed. Conclusion: The results showed that the accumulation of emotions, emotional distress in marital relationships and life tensions, leads to mental exhaustion and eventually leads to marital boredom. Therefore, identifying and paying attention to the predictors of the phenomenon of depression, leads the couple to find effective solutions and prevent the occurrence of this phenomenon. Based on the findings, a model of predictors of marital boredom was designed. Therefore, it is suggested that these indicators be used in the development of counseling protocols in couple therapy.